Green synthesis of silver nanoparticles from plant Fagonia cretica and evaluating its anti-diabetic activity through indepth in-vitro and in-vivo analysis - Khan, Haider Ali; Ghufran, Mehreen; Shams, Sulaiman; Jamal, Alam; Khan, Abbas; Abdullah,; Awan, Zuhier A.; Khan, Mohammad Imran (Frontiers in Pharmacology, 2023)
One of the most widespread metabolic diseases, Type-2 Diabetes Mellitus (T2DM) is defined by high blood sugar levels brought on by decreased insulin secretion, reduced insulin action, or both. Due to its cost-effectiveness and eco-friendliness, plant-mediated green synthesis of nanomaterials has become more and more popular. The aim of the study is to synthesize AgNPs, their characterizations and further in-vitro and in-vivo studies. Several methods were used to morphologically characterise the AgNPs. The AgNPs were crystalline, spherical, and clustered, with sizes ranging from 20 to 50 nm. AgNPs were found to contain various functional groups using Fourier transform infrared spectroscopy. This study focuses on the green-synthesis of AgNPs from Fagonia cretica (F. cretica) leaves extract to evaluate their synthesized AgNPs for in-vitro and in-vivo anti-diabetic function. For the in-vivo tests, 20 male Balb/C albino-mice were split up into four different groups. Anti-diabetic in-vivo studies showed significant weight gain and a decrease in all biochemical markers (pancreas panel, liver function panel, renal function panel, and lipid profile) in Streptozotocin (STZ)-induced diabetic mice. In vitro anti-diabetic investigations were also conducted on AgNPs, comprising α-amylase, α-glucosidase inhibitions, and antioxidant assays. AgNPs showed antioxidant activity in both the DPPH and ABTS assays. The research showed that the isolated nanoparticles have powerful antioxidant and enzyme inhibitory properties, especially against the main enzymes involved in T2DM.